What conclusions should we draw from the data? - Vickers, Andrew (British Homeopathic Journal, 1995)
Critical appraisal of a scientific trial involves deciding on its internal validity— whether the hypothesis has been correctly accepted or rejected—and its external validity—the extent to which the trial's findings can be generalized. Discourse on homoeopathic research has focused on the former at the expense of the latter and an analysis of homoeopathic research demonstrates that it has low external validity. One solution would be to split the research process in two. Large scale, triple-blind trials could be used to determine the extent to which the action of homoeopathy may be explained by placebo. Importantly, no assessment of external validity would be made. Audit and cohort studies could then be used to examine questions usually associated with external validity, such as the conditions most suitable for treatment and the long-term clinical value of homoeopathy.